2008
DOI: 10.1016/j.drugalcdep.2008.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to stop or reduce marijuana use in non-treatment seekers

Abstract: Daily marijuana smokers (n=19) who intended to quit or reduce in the next month on their own called a phone each night for 28 nights to report marijuana use and reported intentions to change at the end of each week. Outcomes did not differ between those who initially planned to reduce vs. quit in the next month. Participants averaged three attempts to reduce and one attempt to quit during the 28 days. Participants reduced on 11% and abstained on 14% of days. Most participants were successful in reducing or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 29 publications
(24 reference statements)
9
42
2
Order By: Relevance
“…The lack of differences found between the abstinence-and moderation-oriented participants are particularly interesting, as they suggest that while the decision to overcome a cannabis problem might be a conscious decision, goal choice at the time of change might be unrelated to the actual recovery orientation pathway that is eventually adopted. In other words, these results suggest that goal choice at the time of change might be a weak predictor of actual recovery orientation, a finding of which is consistent with literature suggesting that goal selection is fluid (Hodgins et al, 1997;Hughes et al, 2008;Ladouceur et al, 2009;Lozano et al, 2006;Ojehagen & Berglund, 1989), and that initial goal selection might be a poor predictor of outcome ).…”
Section: Reasons For Resolutionsupporting
confidence: 80%
See 4 more Smart Citations
“…The lack of differences found between the abstinence-and moderation-oriented participants are particularly interesting, as they suggest that while the decision to overcome a cannabis problem might be a conscious decision, goal choice at the time of change might be unrelated to the actual recovery orientation pathway that is eventually adopted. In other words, these results suggest that goal choice at the time of change might be a weak predictor of actual recovery orientation, a finding of which is consistent with literature suggesting that goal selection is fluid (Hodgins et al, 1997;Hughes et al, 2008;Ladouceur et al, 2009;Lozano et al, 2006;Ojehagen & Berglund, 1989), and that initial goal selection might be a poor predictor of outcome ).…”
Section: Reasons For Resolutionsupporting
confidence: 80%
“…Specifically, as alluded to previously in this manuscript, Hughes et al (2008) reported that among 19 non-treatment seeking daily cannabis users who intended to quit or reduce on their own in the next month, initial goal selection was a poor predictor of outcome, most users made multiple and short-lived attempts to change, reduced use was as common as abstinence, many attempts to change were initially successful but few persisted, and other drug use did not appear to worsen with reduced use or abstinence. Stephens et al (1994a) tested the abstinence violation effect (AVE; Marlatt & Gordon, 1980) among a sample of 75 adult cannabis users who reported a lapse into cannabis use following completion of either a relapse prevention treatment or social support group treatment.…”
Section: Overview In the Cannabis Use Disorders Literaturementioning
confidence: 99%
See 3 more Smart Citations